2011
DOI: 10.15517/rgac.v0i47.6484
|View full text |Cite
|
Sign up to set email alerts
|

Geología y estratigrafía de la hoja 3246-ii miramar, costa rica

Abstract: The oldest rocks of the Miramar sheet are represented by sediments of the Punta Carballo Formation (Miocene), which are exposed at the SW corner. However, volcanic rocks of the older Aguacate Group (Miocene-Pliocene) and overlying Monteverde Formation (Lower Pleistocene) dominate the area. The Pliocene to Pleistocene silicic ignimbrites and Quaternary sediments are subordinate. New K-Ar ages yielded 4,41±0,15 to 4,99±0,36 Ma for the Aguacate Group and 1,71±0,22 to 1,77±0,11 Ma for the Monteverde Formation. Gab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…We expect that the records of a broadband station have lower self-noise level in the low frequency range in comparison with strong motion records. For this study, we select the station JTS000, administrated by the Costa Rican Vulcanology and Seismology Observatory (OVSICORI) located in Las Juntas, Guanacaste, which is located at a rock site with low amplification (Záček et al 2012). The station has a sampling rate of 40 Hz (http://ds.iris.edu/wilber3/find stations/ 10485770).…”
Section: Seismic Networkmentioning
confidence: 99%
“…We expect that the records of a broadband station have lower self-noise level in the low frequency range in comparison with strong motion records. For this study, we select the station JTS000, administrated by the Costa Rican Vulcanology and Seismology Observatory (OVSICORI) located in Las Juntas, Guanacaste, which is located at a rock site with low amplification (Záček et al 2012). The station has a sampling rate of 40 Hz (http://ds.iris.edu/wilber3/find stations/ 10485770).…”
Section: Seismic Networkmentioning
confidence: 99%
“…The SNR is defined here as the larger PGA of the two horizontal components divided by the noise level (RMS amplitude of the two horizontal components in the time domain at the pre-P-waves part of the records). [26] In this study, we used the Sixaola sites shown in Table 1 only to reproduce the acceleration spectra at sites related to the mentioned intensity anomaly or located above the source of the 2012 Sámara earthquake.…”
Section: Data Processingmentioning
confidence: 99%
“…We expect that the records of a broadband station have lower self-noise level in the low frequency range in comparison with strong motion records. For this study, we select the station JTS000, administrated by the Costa Rican Vulcanology and Seismology Observatory (OVSICORI) located in Las Juntas, Guanacaste, which is located at a rock site with low amplification ( Žáček et al, 2010) [26]. The station has a sampling rate of 40 Hz (http : //ds.iris.edu/wilber3/f ind s tations/10485770).…”
Section: Seismic Network and Data Processing 31 Seismic Networkmentioning
confidence: 99%
“…Sin embargo, existe una amplia variabilidad en cuanto a la importancia relativa de la neotectónica dentro de los estudios evaluados. En un buen número de casos se encuentra que se hacen inferencias neotectónicas, como parte de estudios de cartografiado geológico reportados (p. e., Denyer & Arias, 1993;Žáček et al, 2012;Alvarado et al, 2009;Obando & Kussmaul, 2009). En otras publicaciones, se realizan interpretaciones neotectónicas para explicar diferentes hallazgos, determinados a partir de diversas ramas de la geología, como son la hidrogeología (p.e., Vargas & Fernández, 2002;Herrera & Orosco, 2010), o la sedimentología (Alvarado, 2009;Cárdenes, 2003), entre otras.…”
Section: Discusión Y Conclusionesunclassified
“…Entre estos se destacan los trabajos de cartografiado geológico (Alvarado, 2009;Alvarado et al, 2009;Obando & Kussmaul, 2009;Žáček et al, 2012). En el noroeste de Costa Rica, es importante destacar el trabajo de Montero & Denyer, 2011), tanto porque cubre una zona amplia, como es la penínsu-la de Nicoya, como por el modelo neotectónico que proponen para explicar el arreglo de fallas y pliegues determinado.…”
Section: Discusión Y Conclusionesunclassified